The effect of the number of interviewers on children’s testimonies - Ferra, Fenia (Psychology, crime & law, 2022)
Many investigative interviews with children who report that they have been victims of crime are carried out by one interviewer. Some interviews, however, may involve more than one interviewer. There has been little research examining the impact upon children’s reports when more than one interviewer (or adult) is present. Over the course of two experimental studies, involving 375 children in total, the effects that the number of adults (present in such interviews) had on children’s recall were investigated. It was found that the number of the adults present during an interview had an effect on the quality and quantity of the information children provided. When children were interviewed by a single interviewer, with no-one else present, the children provided lengthier and more accurate accounts, in comparison to when children were interviewed by an interviewer in the presence of either one or two additional adults. These findings have implications for the conduct of forensic interviews, especially in those countries where several adults are present in forensic interviews.